Antifungal activity of essential oils from Iranian plants against fluconazole-resistant and fluconazole-susceptible Candida albicans - Aghil Sharifzadeh; Hojjatollah Shokri (Mashhad University of Medical Sciences, 2016)
Objectives: The purpose of this study was to assay the antifungal activity of selected essential oils obtained from plants against both fluconazole (FLU)-resistant and FLU-susceptible C. albicans strains isolated from HIV positive patients with oropharyngeal candidiasis (OPC). Materials and Methods: The essential oils were obtained by hydrodistillation method from Myrtus communis (My. communis), Zingiber officinale roscoe (Z. officinale roscoe), Matricaria chamomilla (Ma. chamomilla), Trachyspermum ammi (T. ammi) and Origanum vulgare (O. vulgare). The susceptibility test was based on the M27-A2 methodology. The chemical compositions of the essential oils were obtained by gas chromatography- mass spectroscopy (GC-MS). Results: In GC-MS analysis, thymol (63.40%), linalool (42%), α-pinene (27.87%), α-pinene (22.10%), and zingiberene (31.79%) were found to be the major components of T. ammi, O. vulgare, My. communis, Ma. chamomilla and Z. officinale roscoe, respectively. The results showed that essential oils have different levels of antifungal activity. O. vulgare and T. ammi essential oils were found to be the most efficient (P